Meiosis-specific stable binding of augmin to acentrosomal spindle poles promotes biased microtubule assembly in oocytes. - Nathalie Colombié; A Agata Głuszek; Ana M Meireles; Hiroyuki Ohkura (PLoS Genetics)
In the oocytes of many animals including humans, the meiotic spindle assembles without centrosomes. It is still unclear how multiple pathways contribute to spindle microtubule assembly, and whether they are regulated differently in mitosis and meiosis. Augmin is a γ-tubulin recruiting complex which "amplifies" spindle microtubules by generating new microtubules along existing ones in mitosis. Here we show that in Drosophila melanogaster oocytes Augmin is dispensable for chromatin-driven assembly of bulk spindle microtubules, but is required for full microtubule assembly near the poles. The level of Augmin accumulated at spindle poles is well correlated with the degree of chromosome congression. Fluorescence recovery after photobleaching shows that Augmin stably associates with the polar regions of the spindle in oocytes, unlike in mitotic cells where it transiently and uniformly associates with the metaphase spindle. This stable association is enhanced by γ-tubulin and the kinesin-14 Ncd. Therefore, we suggest that meiosis-specific regulation of Augmin compensates for the lack of centrosomes in oocytes by actively biasing sites of microtubule generation within the spindle.